BIAYA PEMELIHARAAN DAN HARGA JUAL TERHADAP PENDAPATAN PETANI CENGKEH DI DESA SELALEJO TIMUR - Maria Kristina Sara Daro; Yosef Moan Banda; Stefanus Gusti Ma (Bajang Institute, 2021)
The objectives of this study were (1) determine the cost of maintaining farmers’ income in East Selalejo Village (2) the effect of selling prices on farmers’ income in East Selalejo Village (3) the effect of maintenance costs and selling prices simultaneously on farmers’ income in East Selalejo Village. The research subjects were 30 farmers in the village of East Selalejo and the objects of this research were clove farmers, maintenance costs and selling prices. The type of data from this research is quantitative, the overall information collected is farmers’ income, maintenance costs and selling prices in the village of East Selalejo. The data collection technique used in the study was a questionnaire instrument. The results showed (1) there was an effect of maintenance costs on farmers’ income, (2) there was an effects of selling price on farmers’ income in East Selalejo Village and (3) there was an effect of maintenance costs and selling prices simultaneously on farmers’ income in East Selalejo Village.